Modeling social comparison in the stress process: an examination of nurses - Chlevin, Cassandra (Kansas State University, 2021)
Excessive workplace stress is a costly problem for organizations and a psychophysical hazard to workers. While some sources of stress cannot be avoided or eliminated from certain occupations, they do not always result in stressful experiences for workers. Research is steadily uncovering the factors that influence experiences of workplace stress in hopes of better controlling its harmful outcomes. Accordingly, the present study focused on the potential impact of social comparison on workers’ interpretations of demanding workplace events and their confidence in coping with stress. A sample of 139 healthcare workers provided personal data in relation to five types of stressors common to the field of nursing, along with relevant information about how they perceive their coworkers’ responses to said stressors. Support was found for the hypothesized model through path analysis. Workers reported higher levels of stress when they were 1) frequently exposed to demanding events, and 2) when they perceived high levels of stress in their coworkers. They also felt more prepared to cope with that stress when they reported high familiarity with their coworkers’ coping tactics. However, the more stressed the workers felt, the less prepared they felt to cope overall. The insights offered by these results contribute to the fusion of stress research and social comparison literature. It is hoped that the dissemination of findings like these may inform intervention efforts to help workers manage stress while simultaneously educating them about how they can harness social information to benefit themselves and others. The timing of such efforts is particularly relevant given the COVID-19 global crisis that is exacerbating the difficulties and negative outcomes already associated with medical occupations.
Keywords: Stress; Coping; Social Comparison; Vicarious Learning; Nursing; Workers